2014
DOI: 10.1097/shk.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Heme Oxygenase-1

Abstract: Hepatic ischemia-reperfusion (IR) results in progressive injury, initiated by oxidative stress during ischemia and compounded by cytokine-mediated inflammation during reperfusion. Recovery requires strict regulation of these events. Recombinant human erythropoietin (rhEPO) is thought to mitigate hepatocellular IR injury by altering the non-parenchymal liver microenvironment. This study sought to identify additional mechanisms whereby rhEPO is protective after liver IR injury. Methods Mice were treated with rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…In this regard, previous studies demonstrated the stimulating effect of EPO on HO1 expression in hepatocytes after ischemia/reperfusion injury [45] , neurons [46] , astrocytes [47] and in monocyte of patient under hemodialysis [48] . Moreover, the stimulatory effect of EPO on renal HO1 expression has been described in vivo and in vitro [49] , in addition to the stimulatory effect of HO1 on differentiation of M2 macrophages in models of protection against obesity-induced inflammation [50] , diabetic cardiomypathy [51] , diabetic gastroparesis [52] , colonic inflammation [53] and atherosclerosis [54] .…”
Section: Discussionmentioning
confidence: 90%
“…In this regard, previous studies demonstrated the stimulating effect of EPO on HO1 expression in hepatocytes after ischemia/reperfusion injury [45] , neurons [46] , astrocytes [47] and in monocyte of patient under hemodialysis [48] . Moreover, the stimulatory effect of EPO on renal HO1 expression has been described in vivo and in vitro [49] , in addition to the stimulatory effect of HO1 on differentiation of M2 macrophages in models of protection against obesity-induced inflammation [50] , diabetic cardiomypathy [51] , diabetic gastroparesis [52] , colonic inflammation [53] and atherosclerosis [54] .…”
Section: Discussionmentioning
confidence: 90%
“…Hepatic IR injuries attenuated by EPO administration before 7 and after 19 IR procedures have been reported in animal models. In the current study, the TH+EPO group had a relatively higher GOT level on day 1.…”
Section: Discussionmentioning
confidence: 97%
“…To clarify EPO's ability to restore myocardial function, a prospective study with regular and longer follow-ups of CK and CK-MB levels and cardiac echogram is required. Hepatic IR injuries attenuated by EPO administration before 7 and after 19 IR procedures have been reported in animal models. In the current study, the TH+EPO group had a relatively higher GOT level on day 1.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to erythropoiesis, it is well known that EPO has multiple protective effects and exhibits antiapoptotic, antioxidant, and anti-inflammatory activities as well ( Figure 3 ). Taking advantage of these biological activities of EPO, a number of researchers showed the protective effect of EPO in hepatic ischemia/reperfusion injury [ 84 , 85 , 86 ] that is mediated via the activation of the phosphatidylinositol-3 kinase/AKT/endotherial NO synthase pathway [ 84 ] or the inhibition of caspase-3 activation [ 85 ]. EPO also attenuates systemic ischemia/reperfusion injuries, such as liver and kidney, induced by resuscitation from a massive hemorrhage [ 87 , 88 ].…”
Section: Lactoferrinmentioning
confidence: 99%